Directed evolution of Thermomyces lanuginosus lipase to enhance methanol tolerance for efficient production of biodiesel from waste grease - Tian, K.; Tai, K.; Chua, B. J. W.; Li, Z.
Engineering a methanol tolerant lipase is of great importance in biodiesel production. Here, the first semi-rational method for directed enzyme evolution to enhance methanol tolerance by targeting high B-factor residues for iterative saturation mutagenesis (ISM)is reported. The best double mutant, TLL-S105C/D27R, retained 71 percent of its original activity after incubation in methanol, showing 30 percent greater methanol tolerance than TLL. TLL-S105C/D27R also displayed 27 percent higher activity over TLL. Structure modelling suggested that the increased stability of TLL-S105C/D27R was caused by the formation of a new hydrogen bond which stabilized the protein structure. E. coli (TLL-S105C/D27R)-catalyzed biotransformation of waste grease produced biodiesel in 81 percent yield in 8h, showing improvement over the 67 percent yield for E. coli (TLL), while retaining 92 percent productivity after 4 cycles of biotransformation of waste grease. The engineered TLL mutant shows high potential for commercial biodiesel production
Keywords: B-FACTOR; BIODIESEL; DIRECTED EVOLUTION; METHANOL TOLERANCE; THERMOMYCES LANUGINOSUS LIPASE